Computational study of compound angle film cooling flow field and aerodynamic losses using a parallel hybrid mesh Navier–Stokes code. (September 2015) - Luo, Chang; Misaka, Takashi; Obayashi, Shigeru; Goto, Takashi; Yamawaki, Ruriko
Flow characteristics and aerodynamic losses of film cooling injection with compound angles of 30°, 60°, and 90° for velocity ratios of 0.5, 1.0, and 2.0 are numerically investigated using the high-quality hybrid meshes comprising tetrahedrons, prisms, and pyramids. The solutions are obtained by solving the compressible Reynolds-averaged Navier–Stokes equations, and the cell-vertex finite volume method is used to discretize these equations. The predicted results are firstly validated against the experimental data. It has been found that the variation tendency of mass average net total pressure loss coefficient with compound angles is reasonably predicted and in many cases well predicted. The analyses based on net total pressure losses show that the aerodynamic losses tend to increase with the increasing of compound angle regardless of the velocity ratio, and the tendency becomes more obvious when the velocity ratio is large. On the other hand, some typical cases are additionally calculated with different turbulence models and flux computation schemes for the comparisons. A latest proposed numerical flux computation method, simple low-dissipative AUSM (SLAU) scheme, is adopted in the predictions. The results indicate that SLAU scheme is slightly superior to Harten–Lax–van Leer–Einfeldt–Wada scheme in the prediction of compound angle film cooling injection.